WRITING A SCIENTIFIC ARTICLE OR TELLING MEASURED LIES - Khadija Iqbal; Amena Rahim (Journal of University Medical & Dental College, 2013)
ABSTRACT The scientists have a reputation of honesty and dignity and anyone who has ever falsified research is probably unwilling to reveal it. Medical journals are published to promote research in medicine for betterment of the public health. Plagiarism has been pointed before in journals but this study aims to bring certain new things under the discussion of falsification in medical publications. Objective of study was to highlight different points regarding medical writing which should also be included in the domain of plagiarism. Data was collected from 40 different researchers of Pakistan in past five years. The names and institutions were kept confidential. Three researchers admitted that they altered patients statistics. Twenty three out of forty did the same research as done before. Thirty researchers copied parameters from previous research. Eighteen authors added their names in someone else research. Twenty two hired mostly lab technicians to do lab work for them. Concept of falsifying is becoming a practice among researchers. This includes repetition of research work, hiring someone to do research work and adding the names in someone else research.